Adjustments to Minimum Wages in China: Cost-Neutral Offsets - Wang, Jing; Gunderson, Morley (Relations industrielles / Industrial Relations, 2015)
SummaryBased on qualitative interviews of workers, managers and labour inspectors in China, we examine how employers adjust, often in subtle fashions, to minimum wage increases. Our findings highlight the “law of unintended consequences” in that their effects are often “undone” or offset by subtle adjustments such as reductions in fringe benefits and in overtime work and overtime pay premiums that are otherwise valued by employees. Employees often feel that they are no better off in spite of minimum wage increases because of these offsetting adjustments.This study also suggests possible reasons for the small or zero effect of minimum wage on employment in China. Lack of enforcement may be one of the reasons, but the employees we interviewed seem well aware of the legal minimum wage and employers do not want to get involved in disputes over this matter. For employers who would otherwise be affected by the minimum wage increase, the cost increase is mitigated by the offsetting adjustments. As a result, minimum wages do not seem to weaken the competitive position of employers in China.